Anatomy of an epidemic : magic bullets, psychiatric drugs, and the astonishing rise of mental illness in America - Whitaker, Robert (New York : Crown Publishers, 2010)
In this astonishing and startling book, award-winning science and history writer Robert Whitaker investigates a medical mystery: Why has the number of disabled mentally ill in the United States tripled over the past two decades? Every day, 1,100 adults and children are added to the government disability rolls because they have become newly disabled by mental illness, with this epidemic spreading most rapidly among our nation’s children. What is going on?

Anatomy of an Epidemic challenges readers to think through that question themselves. First, Whitaker investigates what is known today about the biological causes of mental disorders. Do psychiatric medications fix “chemical imbalances” in the brain, or do they, in fact, create them? Researchers spent decades studying that question, and by the late 1980s, they had their answer. Readers will be startled—and dismayed—to discover what was reported in the scientific journals.

Then comes the scientific query at the heart of this book: During the past fifty years, when investigators looked at how psychiatric drugs affected long-term outcomes, what did they find? Did they discover that the drugs help people stay well? Function better? Enjoy good physical health? Or did they find that these medications, for some paradoxical reason, increase the likelihood that people will become chronically ill, less able to function well, more prone to physical illness?

This is the first book to look at the merits of psychiatric medications through the prism of long-term results. Are long-term recovery rates higher for medicated or unmedicated schizophrenia patients? Does taking an antidepressant decrease or increase the risk that a depressed person will become disabled by the disorder? Do bipolar patients fare better today than they did forty years ago, or much worse? When the National Institute of Mental Health (NIMH) studied the long-term outcomes of children with ADHD, did they determine that stimulants provide any benefit?

By the end of this review of the outcomes literature, readers are certain to have a haunting question of their own: Why have the results from these long-term studies—all of which point to the same startling conclusion—been kept from the public?

In this compelling history, Whitaker also tells the personal stories of children and adults swept up in this epidemic. Finally, he reports on innovative programs of psychiatric care in Europe and the United States that are producing good long-term outcomes. Our nation has been hit by an epidemic of disabling mental illness, and yet, as Anatomy of an Epidemic reveals, the medical blueprints for curbing that epidemic have already been drawn up.
A modern plague -- Anecdotal thoughts -- The roots of an epidemic -- Psychiatry's magic bullets -- The hunt for chemical imbalances -- A paradox revealed -- The benzo trap -- An episodic illness turns chronic -- The bipolar boom -- An epidemic explained -- The epidemic spreads to children -- Suffer the children -- The rise of an ideology -- The story that was ... and wasn't told -- Tallying up the profits -- Blueprints for reform.
Bibliografija. - Kazalo
Keywords: Mental illness -- United States; Psychotropic drugs -- United States; Drugs -- Prescribing -- United States; Psychiatry -- United States; Psychiatry -- ethics -- United States; Psychiatry -- history -- United States; Psychology, Pathological -- drug therapy -- United States; Psychology, Pathological -- epidemiology -- United States; Mental illness -- drug therapy -- United States; Psychiatric epidemiology -- United States; mentalne bolesti; terapija ljekovima; psihijatrija